A construção de notícias no twitter: ciberacontecimentos, fluxos e apropriações jornalísticas - Höehr, Kellen Mendes (Universidade do Vale do Rio dos Sinos, 2013)
This study aims to take the path of news construction on Twitter from flows of information developed on the platform and use that journalism makes of them. Through the movement of the actors in the network and intense processes of negotiation and translation of messages, there is a set of symbolic exchanges that are resignified all the time, generating a semiotic stream characterized by the power struggle and visibility within the network. The proposed hypothesis is that some events already have in their constitution elements of digital social networks that allow them to proliferate more strongly within that semiospheric environment. For this, two events were observed in the range of unpredictable, reflected as phenomenon of social networks: the nearly separation of the singers Zezé Di Camargo and Luciano, where the analysis focused exclusively on the journalistic appropriation of the case and meme Luiza in Canada, observed according to its construction on Twitter, the developed flows and journalistic appropriation. From a qualitative analysis of collected materials and from the concepts of semiotics of culture and language, we propose a reflection on the environment where these processes are settle that trigger diffuse agendas between the public and the media and reveal new cultural phenomena in society.
Keywords: Jornalismo; Twitter; Ciberacontecimentos; Semiose; Fluxos; Journalism; Ciberevents; Semiosis; Flows; ACCNPQ::Ciências Sociais Aplicadas::Comunicação